101 strategies for recruiting success : where, when, and how to find the right people every time - Pritchard, Christopher W., 1954- (American Management Association, 2007)
A critical factor in your organization's success is your ability to hire -- and keep -- good people. But in order to tackle the toughest recruiting assignments and keep your company running smoothly with great hires who are there for the long haul, you need to infuse both common sense and corporate street smarts into your approach. 101 Strategies for Recruiting Success offers tips of the trade from a recruiting professional with more than two decades of experience. The book includes proven ways to reel in great talent, including how to make your general recruiting operations proactive rather than reactive, 25 ways to find the people your company needs, methods for conducting interviews and evaluating candidates, advice on how to recruit for diversity, retention tactics such as mentoring, performance appraisal, and anti-raiding strategies that begin before the candidate is hired, and a Recruiting Excellence Workbook.